2014
DOI: 10.1016/j.bbi.2014.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Emotional regulatory function of receptor interacting protein 140 revealed in the ventromedial hypothalamus

Abstract: Receptor-interacting protein (RIP140) is a transcription co-regulator highly expressed in macrophages to regulate inflammatory and metabolic processes. However, its implication in neurological, cognitive and emotional conditions, and the cellular systems relevant to its biological activity within the central nervous system are currently less clear. A transgenic mouse line with macrophage-specific knockdown of RIP140 was generated (MΦRIPKD mice) and brain-region specific RIP140 knockdown efficiency evaluated. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Therefore, RIP140 seems to be able to adopt various mechanisms to provide a feedback control for multiple critical physiological processes. Gene knockout/silencing studies in animals reveal numerous abnormal phenotypes in the mouse . Most interestingly, behavior phenotypes are commonly observed in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, RIP140 seems to be able to adopt various mechanisms to provide a feedback control for multiple critical physiological processes. Gene knockout/silencing studies in animals reveal numerous abnormal phenotypes in the mouse . Most interestingly, behavior phenotypes are commonly observed in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…For most transcription factors, RIP140 acts as a corepressor by recruiting various repressive enzymes/factors such as HDACs, CtBP, and G9a, and so forth . Animal studies have revealed its diverse functions in various biological/physiological processes including energy expenditure, behavior, immunity, lipid metabolism, insulin signaling, and neuron stress, and so forth . In the RA‐induced ESC differentiation process, RIP140 is required for the Brg/Brm switch on the Nanog and Oct4 gene promoters when they are silenced in differentiating cells .…”
Section: Introductionmentioning
confidence: 99%
“…1306A30679). All behavioral assessments were performed as previously described (Flaisher-Grinberg et al, 2012, Flaisher-Grinberg et al, 2014). The general activity was assessed by the automated open field environments.…”
Section: Methodsmentioning
confidence: 99%
“…Receptor-interacting protein 140 (RIP140), a transcriptional co-regulator for numerous transcription factors and a signal transduction regulator, is recently implicated in the regulation of cognitive function, emotional response and neuron health via its activities in microglia and neurons (Feng et al, 2014, Flaisher-Grinberg et al, 2014). RIP140 is first known to co-regulate the activities of many nuclear receptors/transcription factors that regulate lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation